Investigation of resin composition and printing parameters on the dimensional accuracy of alumina components fabricated via ceramic vat photopolymerization - Piie Konnunaho; Setareh Zakeri; Erkka J. Frankberg; Erkki Levänen (Open Ceramics)
Dimensional accuracy in ceramic vat photopolymerization is influenced by broadening, where cured regions exceed intended exposure areas due to light scattering in the ceramic resin. This study evaluates how printing parameters (exposure time and peel-off speed) and resin composition (photoinitiator type and concentration, and dye type and concentration) affect the accuracy of negative (e.g., holes) and positive (e.g., pillars) features of varying sizes (0.45 mm). Results showed that feature size influences accuracy, with longer exposure times improving interlayer bonding but reducing resolution. Photocuring behavior aligned with the UV absorption spectra of photoinitiators and dyes. Increasing photoinitiator concentration led to higher lateral light penetration (Sw) but lower depth penetration (Dp), while increasing dye concentration resulted in reduced Sw and Dp. The findings in this study enhance the understanding of ceramic VPP, reinforcing its potential for industrial applications that require high dimensional accuracy.